2010
DOI: 10.1002/gj.1194
|View full text |Cite
|
Sign up to set email alerts
|

Significance of AMS in multilayer systems in fold‐and‐thrust belts. A case study from the Eocene turbidites in the southern Pyrenees (Spain)

Abstract: The anisotropy of magnetic susceptibility (AMS), and other magnetic fabric techniques have been tested in a multilayer system of Eocene turbidites from the Southern Pyrenees. The identified magnetic fabrics can be grouped into (1) fabrics related to layer parallel shortening (LPS) acquired in pre-folding conditions, (2) fabrics related to cleavage development and (3) fabrics related to shear parallel to the thrust movement and intermediate cases. AMS depends on (i) the paramagnetic contribution to the suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…100 Ma chemical remagnetization process, and aligning according to the general extension direction during this stage. Several works (Sagnotti et al, 1998;Parés, 2004;Pueyo-Anchuela et al, 2010;Dudzisz et al, 2018, among others) have indicated a relationship between phyllosilicate-related RT-AMS and compression in weakly deformed rocks, with the development of a RT-AMS defined by k max parallel to the strike of compressional structures and to the intersection lineation, keeping their k min perpendicular to bedding. The increase of flattening develops a transition to tectonic magnetic fabrics in which k min becomes perpendicular to cleavage planes.…”
Section: Tectonic Meaning Of Ams In Relation To Basin Evolutionmentioning
confidence: 99%
“…100 Ma chemical remagnetization process, and aligning according to the general extension direction during this stage. Several works (Sagnotti et al, 1998;Parés, 2004;Pueyo-Anchuela et al, 2010;Dudzisz et al, 2018, among others) have indicated a relationship between phyllosilicate-related RT-AMS and compression in weakly deformed rocks, with the development of a RT-AMS defined by k max parallel to the strike of compressional structures and to the intersection lineation, keeping their k min perpendicular to bedding. The increase of flattening develops a transition to tectonic magnetic fabrics in which k min becomes perpendicular to cleavage planes.…”
Section: Tectonic Meaning Of Ams In Relation To Basin Evolutionmentioning
confidence: 99%
“…The general assumption that finer grain-size levels (e-level) can be more sensitive to strain is evident at outcrop scale, where penetrative cleavage is better developed in e-level with respect to sandstones. The comparison with other magnetic fabrics in these zones shows the coexistence of complex magnetic fabrics, with more paramagnetic fabrics (LTAMS, AGRM) linked to cleavage, intersection lineation or folding (Oliva-Urcia et al, 2009;Pueyo Anchuela, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Bulk susceptibility shows for the different Bouma analyzed levels values between 20 and 385 Â 10 À6 (SI Ferromagnetic particles are mainly related to magnetite and no significant high coercivity mineral phases are present in the studied rocks (Pueyo Anchuela et al, 2010). The comparison of the susceptibility at different fields (0, 1,…”
Section: Magnetic Carriersmentioning
confidence: 94%
See 1 more Smart Citation
“…Pueyo Anchuela et al . , 2010). While samples from Nasiczne had a distinctly stronger magnetic remanence compared with other sites (Fig.…”
Section: Discussionmentioning
confidence: 99%